EXPERIENCES OF PATIENTS TREATED IN THE REANIMATION UNIT REGARDING PAIN EXPERIENCE, ADEQUATE PAIN ASSESSMENT AND PAIN ALLEVIATION - Pejaković, Jasmina; Vicković, Sanja (Acta medicae Medianae, 2023)
An intensive care and reanimation unit (ICU) is a hospital ward that provides optimal care and treatment for critically ill patients. The reanimation unit is a very stressful environment for patients. Aims of the study were to evaluate and identify the pain experience of ICU patients and adequate assessment of pain. This study was conducted as a prospective, observational study involving 121 patients treated in the Reanimation Department, Emergency Center, Clinical Center of Vojvodina. All the examined patients over 18 years of age hospitalized in this Department who met inclusion criteria were interviewed at the bedside. Data were collected by using the questionnaire filled in by a doctor during their conversation with a patient. Thirty-two point two percent of patients were hospitalized from 3 to 7 days, the same percentage of patients were hospitalized for more than 7 days, while 21.5% were hospitalized 1–3 days and 14.1% for one day. Sixty-one point eight percent of the patients reported inability of speech, 14.5% of patients stated their inability of speech and not knowing who to refer to as a problem. Sixty-four point four six percent of patients received analgesic therapy soon after complaining of pain, while 4.13% of patients reported not having analgesics after complaining of pain. Eighty-four point one percent of patients received therapy intravenously. Fifty-six percent of patients answered positively and 3.5% of patients were not satisfied with prescribed analgesics. Fifty-five point three seven percent of patients had the strongest daytime pain. Many factors contributed to increased pain intensity: the extent of performed surgical treatment, surgical wound, injuries and fractures, numerous medical procedures, prolonged immobility in bed and back pain as a consequence.
Keywords: pain, intensive care, reanimation, analgetic treatment